Feasibility Study: Effect of Sample Pre-Treatment Procedures on Creatinine Results and Overall Implication on Downstream Diagnosis of Inherited Metabolic Disorders - Derylize Beukes; Talulani Marageni; Vutomi Mathevula (Journal of Inborn Errors of Metabolism and Screening)
Abstract Introduction: Creatinine (Cr) is a chemical waste breakdown product of creatine and Cr levels can assist in diagnosing the functioning of the kidneys and it can be measured as part of basic- or comprehensive metabolic panel tests. Urinary creatinine (UCr) is often used to calculate urine analyte concentrations of metabolic panel tests, which emphasizes the need for infallibly accurate UCr results. Methods: Cr analysis was performed using an enzymatic Cr analysis kit. A total of four ERNDIM EQA urine samples with known Cr values and four samples with unknown Cr values were used in this study. Results: For the known Cr value samples, a percentage difference from the known value was calculated for each comparison. The rotated and centrifuged result comparison showed the lowest % difference from the known UCr value for known samples 1 and 4: 0.31% and 0.34% respectively. The centrifuged comparison showed lower % differences compared to those of the initial and repeat results. For the unknown UCr value samples results, standard deviations, averages and %CV (coefficient of variance) were calculated. Conclusion: This feasibility study, however small, is suggestive proof that there is indeed necessity and room for optimization when it comes to standardisation of pre-treatment procedures prior to UCr analysis.